Educational-methodical complex as a modern didactic tool for managing students’ independent work in the study of physics - Коновал, О. А. (Pedagogy of Higher and Secondary Education, 2012)
Konoval A. A. Educational-methodical complex as a modern didactic tool for managing students’ independent work in the study of physics. In article approaches to designing of modern didactic means of the organisation and management of independent work of students reveal at physics studying; the content moves, appointment of components of uchebno-methodical complexes which should provide effective support of independent work of students reveals.